Casein kinase 2 attenuates brain injury induced by intracerebral hemorrhage via regulation of NR2B phosphorylation - Sun, Zhimin; Li, Qiyao; Li, Xiaopeng; Shi, Yunpeng; Nan, Chengrui; Jin, Qianxu; Wang, Xiaoyan; Zhuo, Yayu; Zhao, Zongmao (Frontiers in Cellular Neuroscience, 2022)
Objective Intracerebral hemorrhage (ICH) is a common cerebrovascular disease with high incidence, disability, and mortality. Casein kinase 2 (CK2) is a serine/threonine kinase with hundreds of identified substrates and plays an important role in many diseases. This study aimed to explore whether CK2 plays protective roles in ICH-induced neuronal apoptosis, inflammation, and oxidative stress through regulation NR2B phosphorylation. Methods CK2 expression level of brain tissues taken from ICH patients was determined by immunoblotting. Neurons from embryonic rat and astrocytes from newborn rats were cultured and treated by Hemoglobin chloride (Hemin). The proliferation of astrocytes, the apoptosis and oxidative stress of neurons and the inflammatory factors of astrocytes were detected. CK2 expression was determined in ICH model rats. The effects of CK2 overexpression plasmid (pc-CK2) on neurobehavioral defects and brain water content in ICH rats were observed. Results CK2 expression in ICH patients was down-regulated. Overexpression of CK2 promoted the astrocyte proliferation, inhibited neuronal apoptosis, and reduced astrocyte-mediated inflammation. N-methyl-D-aspartate receptor 2B (NR2B) reversed the effects of pc-CK2 on neurons and astrocytes. CK2 phosphorylated NR2B at the S1480 site, down-regulated the expression of NR2B and interfered with the interaction between NR2B and postsynaptic density protein 95 (PSD95). In vivo experiments showed that the expression of CK2 decreased and the expression of NR2B increased in ICH rats. Furthermore, pc-CK2 attenuated neurobehavioral defects, brain water content and neuronal damage in ICH rats. Conclusion CK2 phosphorylated NR2B, down-regulated the expression of NR2B, interfered with the interaction between NR2B and PSD95, alleviated inflammatory reactions, inhibited neuronal apoptosis and oxidative stress after ICH. CK2 and NR2B may be new potential therapeutic targets for the treatment of ICH. However, the limitation of this study is that we only investigated the regulation of NR2B by CK2.